2019
DOI: 10.1021/acs.orglett.9b00017
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Compatible [3 + 2] Nitrone–Olefin Cycloaddition Suitable for DEL Syntheses

Abstract: The limited scope of DNA-compatible chemistry restricts the types of chemical features that can be incorporated into DNA-encoded libraries (DELs). Here, a method to synthesize DNAconjugated polycyclic isoxazolidines via a [3+2] nitrone-olefin cycloaddition is described. The reaction is compatible with many olefin-containing substrates and diverse N-alkylhydroxylamines. The ability to perform subsequent DNA ligation and PCR amplification was also confirmed. This methodology facilitates the synthesis of DELs con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…These considerations lead us to predict that to access more elaborate, higher cycle number DELs, developers will begin to deemphasize current workhorse reactions such as peptide bond formation (at least acylation of secondary amines) in favor of true "freebies" that incur little or no DNA damage. These would include reductive aminations, 81 pericyclic reactions 84 and organocatalytic processes 72,73 , amongst others. Another exciting possibility is to adapt enzyme-catalyzed transformations to DEL synthesis.…”
Section: Dna Is Not Teflon: the Importance Of Quantitative Assessmentmentioning
confidence: 99%
“…These considerations lead us to predict that to access more elaborate, higher cycle number DELs, developers will begin to deemphasize current workhorse reactions such as peptide bond formation (at least acylation of secondary amines) in favor of true "freebies" that incur little or no DNA damage. These would include reductive aminations, 81 pericyclic reactions 84 and organocatalytic processes 72,73 , amongst others. Another exciting possibility is to adapt enzyme-catalyzed transformations to DEL synthesis.…”
Section: Dna Is Not Teflon: the Importance Of Quantitative Assessmentmentioning
confidence: 99%
“…By combining innovative library design based on the constant development of new chemistries [15,16,17,18] with carefully crafted building block collections [19], DNA-encoded libraries are largely comprised of members with favorable drug-like properties, both regarding their molecular and physical chemistry features. In addition, opposed to some hits selected from classical HTS formats, which partially resemble natural product derivatives, DEL-derived leads all have the benefit of being mostly accessible due to the well validated synthesis procedures.…”
Section: Dna-encoded Librariesmentioning
confidence: 99%
“…In an unprecedented utilization of these building blocks, Schreiber and co‐workers developed a method for the synthesis of DNA‐encoded libraries (DELs), that is, DNA‐conjugated polycyclic isoxazolidines ( 170 ). The reaction proceeded through a [3+2] nitrone–olefin cycloaddition . The authors demonstrated the ability to perform DNA ligation and PCR amplification on the designed library.…”
Section: Divergent Synthesis Of Various Polycyclic Compoundsmentioning
confidence: 99%
“…The reactionp roceeded through a[ 3 + +2] nitrone-olefin cycloaddition. [66] The authors demonstrated the ability to perform DNA ligationa nd PCR amplification on the designed library.T his elegantm ethodology delivered topographically complex compoundsw ith underexplored chemical space and serves to fill some of the structural and functional gaps left by current on-and off-DNA small-molecule libraries (Scheme40).…”
Section: Synthesis Of Benzopyran-annulatedsystemsmentioning
confidence: 99%